Crossover of the patient satisfaction surveys, adverse events and patient complaints for continuous improvement in radiotherapy department. (15th March 2022) - Cucchiaro, SÉverine; Princen, Fabienne; Goreux, JoËlle; Cunin, Marie-Pierre; Jacques, Jessica; Delgaudine, Marie; Coucke, Philippe Antoine
Abstract: Objective: The patient's needs and expectations can be assessed through satisfaction surveys, adverse event declarations and records of complaints. By cross-referencing individual complaints, satisfaction surveys and the adverse events received, we could get valuable information. The objective is to identify common elements of work between these different sources to improve care. Methods: A retrospective analysis of patients' complaints, surveys and adverse events was carried out in order to highlight common improvement items between these three sources of information. Results: A satisfaction survey was given to the patients at the end of their treatment, who filled it out and left it in the 'ad hoc' letterbox. At the end of December 2019, 4695 questionnaires had been collected (response rate 37%). In addition, since 2014, 1369 patients (∼20 patients per month) have been interviewed 'face to face' by the research nurse who assesses their satisfaction using open questions. At the same time, a collection of complaints and adverse events was carried out. All these data have been analysed and cross-checked in order to highlight areas for improvement and strengthen the safety and quality of care in our department. Conclusions: Collect and analyse satisfaction surveys, unexpected events and complaints constitute in our opinion, an effective tool to achieve patient empowerment. We aim for the patients to become a real player in their safety and involve in the overall effort to improve the quality of their radiotherapy treatment by reporting what does not meet their expectations.